USE OF WATER FACILITIES IN THE DESIGN OF LANDSCAPE DESIGN FACILITIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the requirements for modern water facilities, modern trends in the design and construction of water facilities, the design of hydroparks and water parks. And at the end of the article the final conclusions and concepts are given.